A comfortability and signal quality study of conductive weave electrodes in long-term collection of human electrocardiographs. Issue 11 (June 2019) - Xiao, Xueliang; Dong, Ke; Li, Chenhao; Wu, Guanzheng; Zhou, Hongtao; Gu, Yanjia
Long-term electrocardiogram (ECG) recording can reveal some vital cardiovascular disorders and provide warning of human sudden cerebral or vascular diseases in advance. This requires high-quality ECG skin electrodes. Gel (Ag/AgCl) electrodes were reported to have good signal quality in ECG acquisition, but easily caused human skin irritation or allergy. Consequently, textile electrodes have attracted more attention for long-term ECG acquisition. In this paper, eight woven fabrics with diverse yarns and weft densities were fabricated in plain and honeycomb structures. The fabrics were investigated in terms of comfortability, fabric–skin contact impedance and acquired bio-signal quality. Honeycomb weave electrodes were measured with a high comfort level from subjective and objective views, including pleasant tactile comfort, high visual acceptance, good air permeability and good heat transfer. Weave electrodes made of all conductive filaments in high density had low skin contact impedance and high-quality ECG signals. An increase of compression load on weave electrodes resulted in a decrease of contact impedance with a high signal quality. A conductive honeycomb weave with unit repeat of 6* 6 warps* wefts presented the highest score of acquired ECG signals of all studied electrodes based on the qualities of the QRS complex, P and T waves, R peak amplitude and variation and signal-to-noise ratio. This study contributes to the future design and fabrication of textile electrodes using honeycomb weave in long-term and real-time collection of human ECGs.